A Sociolinguistics Analysis On Address Terms Found In The Blood Of Olympus Novel And Its Translation - Pribadi, Alvy Mayrina, Dra. Zuhriah Ariatmi, M. Hum (2016)
The research aims at describing the variations of the types of address terms, the equivalence of reasons of choosing the address terms, and the social factors affecting the use of address terms found in The Blood of Olympus novel and its translation. The type of the research is descriptive qualitative research. The data sources are Blood of Olympus novel and its translation Darah Olympus. The data of this research are dialogues containing address terms used by the characters. Technique of collecting data is documentation, the steps are: reading the novel, underlying the dialogues containing address terms, and giving codes of the data. The technique of analyzing data are describing the data into the address terms types by using Tillit's, Chaika's, and Wardhaugh's theory; analyzing the equivalence of the reason of address terms by using Hymes' theory of Ethnography of Communication; analyzing the social factors of the address terms by using Wardhaugh's theory of Social Factors of Addressing. The result of the research shows that firstly, there are fourteen types of address terms found: (1) title (T) which is divided into three types, title of honorific (ToH), title of occupation (ToC), and title of rank (ToR); (2) first name (FN); (3) short first name (SFN); (4) diminutive first name (DFN); (5) last name (LN); (6) full name (FlN); (7) title plus last name (TLN); (8) title plus first name (TFN); (9) endearment (EN); (10) kinship term (KT); (11) mockery term (MT); (12) nickname (NN); (13) teknonym (Tkn); (14) endearment plus first name (EN+FN). Secondly, there are 187 data or 98.94% are equivalent and 2 data or 1.06% are not equivalent. There are eight reasons of choosing address terms: (1) to show intimacy, (2) to show superiority, (3) to show respect, (4) to show anger, (5) to show familiarity, (6) to assert power, (7) to offer solidarity, and (8) to mock. Lastly, there are six social factors affecting the use of address terms: (1) degree of intimacy (DI), (2) rank of other (RO), (3) family relationship (FR), (4) transactional status (TS), (5) occupational hierarchy (OH), and (6) particular occasion (PO).